Tracing steroidogenesis in prostate biopsy samples to unveil prostate tissue androgen metabolism characteristics and potential clinical application. Issue 210 (June 2021) - Hou, Zemin; Yang, Tao; Mei, Zejie; Zhang, Si; Gao, Yuanyuan; Chen, Xi; Tan, Qilong; Zhu, Xuyou; Xu, Chengdang; Lian, Jianpo; Bian, Cuidong; Liu, Ying; et al.
Abstract: Androgens are essential for prostate cancer development. However, steroidogenesis has mainly been investigated in a limited number of prostate cancer cell lines, leading to varied conclusions and elusive clinical significance. Here, we established an ex vivo research platform with fresh biopsy samples transiently cultured with tritium- labelled androgens to trace steroidogenesis in prostate tissues and investigate its potential clinical application. DHEA was confirmed as the major precursor for androgen synthesis in the prostate. Significant amounts of oxidized DHEA and 5α-androstanedione were generated from DHEA in prostate biopsy samples. Prostatic steroidogenesis was independent of other clinical factors. Furthermore, prostatic steroidogenesis was suppressed after androgen deprivation therapy but increased upon treatment resistance, indicating that prostatic steroidogenesis was affected by clinical treatments. Overall, we provide an accessible research platform to characterize steroidogenesis in prostate tissue and indicate the correlation between prostatic steroidogenesis and disease progression.